Effects of Social Capital on Rural Poverty in Nigeria (2007)
Against the backdrop of increasing focus on the use of Local Level Institutions (LLIs) in addressing poverty and the growing literature on impact of social capital on welfare and poverty, this study provides empirical evidence for Nigeria. The study focuses on households’ memberships in LLIs using primary data from 587 households in 6 participating pilot states under the World Bank’s assisted Community-based Poverty Reduction Project (CPRP). Six measures of social capital were identified. These are density of membership, internal heterogeneity of associations, meeting attendance, payment of membership due, labor contribution and decision making. The study reveals that an average household size of 9 participates in at least 3 LLIs. Further, internal heterogeneity reveals some level of diversity in each group while meeting attendance index averaged about 60% for all participating members of households. An average of N4, 254.90 membership due and 43 days of labour are contributed by households to LLIs. The basic data from the study indicate that households with higher social capital are less poor using different dimensions of poverty. The study shows that while a unit increase in household size tend to aggravate poverty by 3.1%, one extra year of educational attainment reduces the extent of poverty by 1.6%. The level of heterogeneity of the associations, meeting attendance index, cash contribution score and the labour contribution score are the key social capital dimensions with dampening effect on poverty, in the order listed, a unit change in each of these dimensions of social capital leads to 0.85, 1.2, 0.82 and 0.3%, respectively. The findings of this study support recent emphasis on investing in social capital. In addition, it has been shown that investments in LLIs need to be part of poverty alleviation programmes